Influence Of Perceived Service Quality, Social Media Marketing Activities And Patient Satisfaction On Patients Revisit Intention At Private Hospitals In United Arab Emirates - Wafi, Shaban M S (2023)
This research examined the relevance of service quality and social media marketing activities in the context of healthcare of the private hospitals in United Arab Emirates. It encompasses the service quality dimensions of (physical environment, customer-friendly staff, communication, reliability, and responsiveness) and the social media marketing activities dimensions of (interaction, informativeness, customization and perceived risk) that can influence patients’ revisit intention, through patient’s satisfaction. The model incorporates two theories; the expectancy-disconfirmation theory and uses and gratifications theory. A total of 213 respondent of patient’s participated in this study from ten approved private hospitals in the United Arab Emirates via survey questionnaire adopted from related literature. Data was collected by using self- administered questionnaire adapted from related literature and then analysed by using structural equation modeling via Smart PLS. Patient’s satisfaction mediate the relationships between physical environment, reliability and responsiveness on revisit intention with no effect for customer friendly staff and communication. Patient’s satisfaction was found to have mediating effect between perceived risk towards revisit intention with no effect for the remaining dimensions. There is a direct relationship between (physical environment, reliability, responsiveness, and perceived risk) and patients’ satisfaction with no effect for customer friendly staff, communication, interactivity, customization and informativeness